Historical and Onomastic Notes - Zadok, Ran
The date of ADD 1110 = Studia Pohl SM 3 337-42; Evidence for the shift ā > ō in Neo-Assyrian, Neo-Вabylonian and Late-Babylonian onomastic material; On the element ’ayya in Neo-Assyrian, Neo-Вabylonian and Late-Вabylonian transcriptions; On some Syro-Palestinian names in Neo-Assyrian transcription.